Wire materials for scanners in the large hadron collider: an unusual materials selection problem - Bigland, H; Huber, J; Veness, R; Cocks, A (Wiley, 2019)
The transverse distribution of particles in the hadron beam of the Large Hadron Collider (LHC) is measured using wire scanners that pass a thin wire through the hadron beam and detect scattered radiation. Increasing demands on beam instrumentation in the LHC leads one to consider the choice of material for the wire. Here, it is shown that this material choice depends on thermal, mechanical, and radiation scattering properties. Simple analytical models are used to develop an Ashby material index for the design problem. It is confirmed that carbon fibers, currently used in several scanners, are high‐performing materials for this application. The key compromises in the material choice are identified. Notably, thermal conductivity and emissivity are relatively unimportant, whereas heat capacity, tolerance of high temperature, and mechanical strength dominate the material index. Potential competitor materials are identified, along with directions to pursue for performance enhancement.